Keynes's Psycho-Economic Law, Wages and Consumption - Alexandru Trifu (Association of Social and Educational Innovation, 2018)
We consider that a milestone of the economic thought is represented in the modern era by John Maynard Keynes. His "revolution" in the theory and practice of Economics has influenced decisively the capitalist economy for four decades of stability and prosperity, until the oil shocks from the 8th decade of the 20th century. Our intention is to link Keynes' Theory of Income with the Happiness Economics in the world of today. to see and understand if the Keynesian theory and practice is still valid, both at macroeconomic level and, mainly, at the individual and household level. A general remark following the day-by-day life, the statistic data regarding the consumption, the economic good sense, is that people spend the money they get, but not all of it. If the particular intention is to get the right position (status), to reach happiness, or stability at the national economy level, it is needed the existence of Savings to ensure future investments and necessary purchases. The answer to the question is positive, both micro and macro level (the latter being an aggregate of the first one), taken into account the specific requirements and conditionalities of the analyzed law.